MEASURING THE DEMOCRATIZATION DEGREE ACCORDING TO LAW NUMBER 42 OF 2008 CONCERNING GENERAL ELECTION OF THE PRESIDENT AND VICE PRESIDENT - I Dewa Made Putra Wijaya (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
This research aims to study the consistency of the Act No 42 of 2008 concerning the generalelection on president and vice president related to the principles of democracy as stipulated inthe constitution of Indonesian republic of 1945. This research uses statutory and conceptualapproaches. The object of the research is the policy of the general election on president and vicepresident. While the subject of it are the parliament and government as legislator. The legalmaterial of the research consists of regulations, books, papers and other supporting literaturewhich will be analyzed through normative-deductive approach. The research discovers that ,firstly the preamble and its main content of the constitution of Indonesian republic of 1945 haveshown the people sovereignty , democratic principle and recognition of human rights; secondly the Act No 42 of 2008 which become the implementing rules of the general election on president and vice president is less consistent to the spirit of the constitution of Indonesian republic of 1945. The policies of the presidential threshold dan the implementation mechanism of the phased general election have reduced the democratic principles on freedom, equality, justice and accountability.Keywords: democratic principles, the general election on president and vice president